2015
DOI: 10.1074/jbc.m115.672097
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Positive Modulator of Glucagon-like Peptide-1 Signaling from Trigonella foenum-graecum (Fenugreek) Seed

Abstract: Background:Fenugreek is an edible plant used to treat diabetes and other disorders. Results: We isolated a new structure in fenugreek that enhances glucagon-like peptide-1 (GLP-1) potency. Conclusion:The antidiabetic plant fenugreek is a rich source of GLP-1 activity-enhancing compounds. Significance: GLP-1 peptide is a target for new drug screening and drug safety studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…In a screening program of edible plant extracts, King et al. found that ethanol extracts from fenugreek seeds enhance GLP‐1 signaling . An active compound (named N55, compound 3 ) with a novel γ‐lactone structure (Figure ) was purified and evaluated in receptor binding and endocytosis assays through insulin release from RINm5F cells.…”
Section: An Overview Of Nonpeptide Pams Of the Glp‐1rmentioning
confidence: 99%
See 4 more Smart Citations
“…In a screening program of edible plant extracts, King et al. found that ethanol extracts from fenugreek seeds enhance GLP‐1 signaling . An active compound (named N55, compound 3 ) with a novel γ‐lactone structure (Figure ) was purified and evaluated in receptor binding and endocytosis assays through insulin release from RINm5F cells.…”
Section: An Overview Of Nonpeptide Pams Of the Glp‐1rmentioning
confidence: 99%
“…An active compound (named N55, compound 3 ) with a novel γ‐lactone structure (Figure ) was purified and evaluated in receptor binding and endocytosis assays through insulin release from RINm5F cells. Compound 3 enhanced GLP‐1, but not exendin‐4‐induced cAMP production, with an EC 50 value of 3.70 μ m , and GLP‐1R endocytosis in a dose‐dependent and saturable manner . They also postulated that compound 3 bound to GLP‐1 peptide or the GLP‐1(7–36) amide binding site simultaneously with the natural ligand.…”
Section: An Overview Of Nonpeptide Pams Of the Glp‐1rmentioning
confidence: 99%
See 3 more Smart Citations